Potensi Keanekaragaman Jenis Burung Untuk Birdwatching di Resort Situgunung dan Resort Cimungkad Taman Nasional Gunung Gede Pangrango - Insan Kurnia; Bagas Aldiantara Mulawi (Universitas Nusantara PGRI Kediri, 2023)
Birds have ecological, economic, and socio-cultural roles. Birdwatching is use of birds for tourism by seeing or hearing bird directly in nature. The GGPNP has potential for developed as a birdwatching destination. The research aims to identify the bird diversity and their distribution for the development of birdwatching at the Situgunung Resort and the Cimungkad Resort, GGPNP. The research was conducted in April-June 2022 in seven tracks using the IPA method. Qualitative data analysis was carried out on the bird status, while quantitative data analysis was carried out for diversity index, evenness index, and encounter opportunities. The bird diversity found was 50 species from 23 families and seven orders spread over seven observation tracks. Thirteen bird species are protected, three species are the CITES Appendix II, and two species are the IUCN Red List. The most common bird species were found on the Orchid Tourism Track while the least were found on the Cimungkad Tourism Track. Natural forest habitats support a wider variety of birds than any other habitat. The diversity index and evenness index are the high category. Most of the bird species fall into the category of very hard to find. All tracks have the potential to be developed as birdwatching routes.